Lower Oligomeric Form of Surfactant Protein D in Murine Acute Lung Injury Induces M1 Subtype Macrophages Through Calreticulin/p38 MAPK Signaling Pathway - Li, Dandan; Pan, Linyue; Zhang, Xiaoju; Jiang, Zhilong (Frontiers in Immunology, 2021)
Surfactant protein D (SP-D) plays an important role in innate and adaptive immune responses. In this study, we found that the expression of total and de-oligomerized SP-D was significantly elevated in mice with LPS-induced acute lung injury (ALI). To investigate the role of lower oligomeric form of SP-D in the pathogenesis of ALI, we treated bone marrow-derived macrophages (BMDMs) with ALI-derived bronchoalveolar lavage (BAL) and found that SP-D in ALI BAL predominantly bound to calreticulin (CALR) on macrophages, subsequently increasing the phosphorylation of p38 MAPK and expression of IL-6, TNF-alpha, IL-10, and CD80. However, anti-SP-D (aSP-D) and anti-calreticulin (aCALR) pretreatment reversed the SP-D binding and activation of macrophages induced by ALI BAL or de-oligomerized rSP-D. Lack of STAT6 in STAT6-/- macrophages resulted in resistance to suppression by aCALR. Further studies in an ALI mouse model showed that blockade of pulmonary SP-D by intratracheal (i.t.), but not intraperitoneal (i.p.) administration of aSP-D attenuated the severity of ALI, accompanied by lower neutrophil infiltrates and expression of IL-1beta and IL-6. Furthermore, i.t. administration of de-oligomerized rSP-D exacerbated the severity of ALI, in association with more pro-inflammatory CD45+Siglec-F(-) M1 subtype macrophages and production of IL-6, TNF-alpha, IL-1beta, and IL-18. The results indicated that SP-D in the lungs of murine ALI was de-oligomerized and participated in the pathogenesis of ALI by predominantly binding to CALR on macrophages and subsequently activating the pro-inflammatory downstream signaling pathway. Targeting de-oligomerized SP-D is a promising therapeutic strategy for the treatment of ALI and acute respiratory distress syndrome (ARDS).